Institusi Hukum Perwakafan Indonesia: Kajian Kelembagaan Badan Wakaf Indonesia (Sejarah dan Struktur Kelembagaan) - Muhammad Luthfi; Yohana Puspitasari Wardoyo; Kukuh Dwi Kurniawan; Fitria Esfandiari; Yaris Adhial Fajrin (Universitas Muhammadiyah Malang, 2022)
Waqf is part of Islamic philanthropy, along with the development of time and circumstances, waqf processes and procedures developed according to the context of the times, not least the development of the rule of law governing waqf law, Law 41/2004 as a new waqf rule in Indonesia, with the spirit of increasing the productivity of waqf assets, and forming nazhir professionalism, then forming a new institution in the waqf world in Indonesia called Badan Wakaf Indonesia (BWI), Hope with the establishment of BWI becomes the main driving force of representation and becomes a medium in increasing waqf assets for the welfare of the people. This paper discusses the history of the institutionalization of BWI institutions and their institutional rules in Law 41/2004. This paper is normative research with a statutory approach and a conceptual approach. The results of the study from this paper state that the history of the institutionalization of BWI is influenced by the factors of the concept of cash waqf and the factor of updating the concept of waqf management which is not only trying to maintain waqf assets but more to make waqf assets more productive. BWI institutional rules based on Law 41/2004 regulate the position, duties, structure, and diversity, the period of service of management, and rules on the performance process of BWI.